Global prevalence of autism spectrum disorder and its gastrointestinal symptoms: A systematic review and meta-analysis - Wang, Jingyi; Ma, Bin; Wang, Jingjing; Zhang, Zeyi; Chen, Ou (Frontiers in Psychiatry, 2022)
Background Autism spectrum disorder (ASD) is a severe public health concern, and Gastrointestinal (GI) symptoms are becoming more common among co-morbidities. The evidence has to be updated depending on differences in different parts of the world. This systematic review and meta-analysis aimed to better understand the existing epidemiological condition and help make health-related decisions. Methods Searches in PubMed, Web of Science, Embase databases are limited to 14 March 2022. We reviewed the global prevalence of ASD and the incidence of GI in people with ASD. Data were extracted by two independent researchers. Literature quality assessment using the National Institutes of Health Study Quality Assessment Tool. Results We discovered that the global pooled prevalence of ASD was 98/10,000 (95% confidence interval, 95%CI: 81/10,000–118/10,000, I2=99.99%, p<0.001), with 48.67% (95%CI: 43.50 –53.86, I2=99.51%) of individuals with ASD reporting GI symptoms. Based on the subgroup analyses, we found a higher prevalence of autism in males (90/10,000, 95%CI: 71/10,000–112/10,000, I2=99.99%) than females (21/10,000, 95%CI:15/10,000–27/10,000, I2=99.99%). Prevalence of pooling is higher in developing countries (155/10,000, 95% CI: 111/10,000–204/10,000, I2=99.87%) than in developed countries (85/10,000, 95%CI: 67/10,000-105/10,000, I2=99.99%). Conclusion The global incidence of ASD and the prevalence of GI symptoms in ASD are both significant. The prevalence of ASD is much higher in men than in women. Further attention to ASD and its related comorbidities will be required in the future to inform coping strategy adaptation.